Efektivitas Pemanfaatan Kelas Ibu Hamil terhadap Pengambilan Keputusan dalam Pelayanan Kesehatan Ibu Anak (KIA) di Kabupaten Klaten Tahun 2022: The Effectivenes of the Use of Maternity Classes on Decision Making in Maternal and Child Health Service in Klaten Regency - Yeni Nurul Ratmawati; Bima Suryantara; Heni Puji Wahyuningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Background: Not yet optimal decision making in maternal and child health services, might be one of the contributed indirectly causes of maternal death. One of the government programs to reduce maternal mortality and improve the health of pregnant women was to hold classes for pregnant women. The research purpose was to determine the effectiveness of the use of pregnant women’s classes on decision making in maternal and child helath services. Methods: The research design used was a true experimental design with a posttest only control design. The research sample was 130 pregnant women. Results: Implementation of classes for pregnant women were effective in increasing use of the MCH handbook, compliance with ANC visits, completeness of BPCR and compliance with taking iron tablets, was not effective in increasing self efficacy in facing childbirth. The results showed that pregnant women who attend classes for pregnant women could increase the MCH handbook by 5,94 times after controlling for the parity , can increase adherence to ANC Visits 10,97 times after controlling for age, maternal education and health insurance, can increase the completeness of BPCR by 16,58 times after controlling for the parity, can increase adherence to taking iron tablets by 13,82 times after controlling for parity . Conclusion: implementation of the class for pregnant women were effective in increasing decision making in maternal and chold health services